1999
DOI: 10.1161/01.str.30.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decline of Cerebral Microemboli of Arterial Origin After Intravenous Acetylsalicylic Acid

Abstract: Background and Purpose-The present study investigated the influence of the antiplatelet agent acetylsalicylic acid (ASA) on cerebral microembolism as detected by transcranial Doppler sonography (TCD). Methods-Nine patients with recent transient ischemic attack or minor stroke of arterial origin were investigated. Eight had not received an antiplatelet or anticoagulant medication before TCD, and in 1 patient a preexisting ASA medication (100 mg/d) had not been changed since the onset of stroke symptoms. An init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 33 publications
6
48
0
4
Order By: Relevance
“…8 By its ability to bind factor VIIa, tissue factor directly activates the coagulation cascade with the generation of thrombin-a strong platelet activator-thereby linking plaque inflammation with arterial thromboembolism. The clinical relevance of these findings are illustrated by the observations of Goertler et al 21 that aspirin application resulted only in partially reduced MES rates. Since one dose of aspirin blocks, almost completely and for several days the platelet's ability to aggregate through the thromboxane pathway, reversibility of the MESblocking effect could not be examined.…”
Section: Platelet Activation Mechanismmentioning
confidence: 78%
“…8 By its ability to bind factor VIIa, tissue factor directly activates the coagulation cascade with the generation of thrombin-a strong platelet activator-thereby linking plaque inflammation with arterial thromboembolism. The clinical relevance of these findings are illustrated by the observations of Goertler et al 21 that aspirin application resulted only in partially reduced MES rates. Since one dose of aspirin blocks, almost completely and for several days the platelet's ability to aggregate through the thromboxane pathway, reversibility of the MESblocking effect could not be examined.…”
Section: Platelet Activation Mechanismmentioning
confidence: 78%
“…We believe that coronary heart disease has a similar etiology and risk factors with artery cerebral infarction, and the presence of coronary atherosclerosis indicated that the incidence of atherosclerosis increases in the neck and head. Studies have shown that antithrombotic treatments, such as antiplatelet, anticoagulant, and defibrinogen, could reduce the ratio of the detection of the first microemboli after stroke (Goertler et al, 1999). With registered large-scale clinical studies, such as the CARESS test (Markus and MacKinnon, 2005) and CLAIR test, we studied the effect of a clopidogrel and aspirin combination treatment on the prognosis of microembolus-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoprotein IIb/IIIa receptor antagonist such as tirofiban infusion has shown to reduce the rate of microemboli and the effect was reversible with the cessation of infusion (Junghans and Siebler 2003). Administration of intravenous and oral acetylsalicyclic acid (ASA) has shown to reduce the frequency of microemboli rapidly (Goertler, Baeumer et al 1999;Goertler, Blaser et al 2001). Several small studies have shown that dual antiplatelet therapy might lead to rapid decline in microembolic frequency (Esagunde, Wong et al 2006).…”
Section: Assessing Efficacy Of Secondary Prophylaxismentioning
confidence: 99%